ANALISIS SEJARAH DAN PERKEMBANGAN TEORI UTILITARIANISME TERHADAP HUKUM INDONESIA - Taufik, Andi Darma; Wahyuni, Fitri; Gunawan, Hendra (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
There are several schools of legal thought in philosophy, including the Natural Law School, the Positive Law School, the Utilitarian Law School, the Historical School, and others. All schools of law have their own concepts as a basis for making laws. In its actualization, these various legal schools exist in the lives of many people, both the international community and Indonesian society. Utilitarianism places benefit as the goal of law. What is meant by usefulness is happiness. Whether a law is good or not really depends on whether the law makes humanity happy or not. This Utilitarian school was pioneered by Jeremy Bentham (1748 – 1832), a philosopher, jurist economist and legal reformer. Bentham was able to weave the